2018
DOI: 10.1002/alr.22122
|View full text |Cite
|
Sign up to set email alerts
|

Lacrimal sac exposure and a superior lateral anterior pedicle flap to improve outcomes of Draf type II and III procedures

Abstract: Draf type II and III procedures with lacrimal sac exposure and a superior lateral anterior pedicle flap are convenient and seem to be effective. However, further studies with larger numbers of patients are needed to verify our technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…Omura et al designed a surgical technique exposing the lacrimal sac and using a superior lateral anterior pedicle flap to cover the exposed bone during the Draf II and III procedures in a series of 19 patients . Overall, the neo‐ostium remained patent in all patients for at least 6 months after these procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Omura et al designed a surgical technique exposing the lacrimal sac and using a superior lateral anterior pedicle flap to cover the exposed bone during the Draf II and III procedures in a series of 19 patients . Overall, the neo‐ostium remained patent in all patients for at least 6 months after these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies described the use of mucosal grafts or pedicle flaps to decrease frontal neo‐ostium restenosis, and the results indicate that the use of these grafts or flaps led to excellent outcomes . However, no comparative studies have been reported.…”
mentioning
confidence: 99%
“…After skeletonizing the skull base and orbit, bilateral superior, and lateral anteriorly-pedicled mucosal flaps were elevated from the frontal process of the maxilla using a Beaver blade and Rosen round knife with integrated suction. 1 The bone over the lacrimal sac was then resected with a 2 mm otologic drill and 1 mm Kerrison rongeur until the lacrimal sac was exposed to maximize the working corridor laterally. The initial steps of an outside-in endoscopic modified Lothrop procedure were then initiated to expose the dermoid cyst.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Pediatric endoscopic sinus and skull base surgery is challenging due to narrow anatomical confines, variable pneumatization of the paranasal sinuses, inter‐carotid distance, and limited instrumentation. However, with the refinement of endoscopic surgical techniques, and the development of new instruments in otolaryngology, the specific challenges of pediatric skull base surgery may be overcome with the adaptation of these techniques, and the adoption of new instruments 1,2 . The objective of this article is to present a novel technique using endoscopic ear instrumentation and a modified Draf III approach for the resection of a nasal dermoid cyst with an intracranial component that is applicable to the pediatric patient without frontal sinus pneumatization, and with narrow nasal cavities.…”
Section: Introductionmentioning
confidence: 99%
“…To speed up mucosal healing and prevent osteitis, mucosa flaps can be used to cover exposed bone [15]. Several mucosal flaps applied to Draf procedures were reported varied from free grafts to pedicled flaps [2,5,11,[16][17][18][19][20]. A free graft is easy to manipulate but is lacking in viability.…”
Section: Introductionmentioning
confidence: 99%